ANALISA PERLAKUAN AKUNTANSI PERSEDIAAN BARANG DAGANGAN PADA PT. TATA BUSANA JAKARTA - Pujiwidodo, Dwiyatmoko (Universitas Bina Sarana Informatika, 2015)
The main purpose of a business activity is generating as much profit as possible. In a trading company, the sale of merchandise is a major source of profit. Therefore, the company should be able to manage the resources they have to make the right policies, especially policies in terms of merchandise inventory accounting treatment. The role played by inventory leads to errors in the accounting treatment of stock merchandise will directly influence the presentation of the financial statements. Statement of Financial Accounting Standards (SFAS) No. 14 explains how the accounting treatment for inventories. During this PT. Tata Busana not conduct a review of the accounting treatment for inventories of merchandise customized with SFAS no. 14. Therefore, it is necessary to analyze the accounting treatment for inventories at PT. Tata Busana, whether in accordance with SFAS No. 14. The data obtained using the documentation and observation techniques. Analysis of the data is to use a comparison of inventory accounting perlakun PT. Tata Busana with SFAS No. 14. PT. Tata Busana is a company engaged in the field of Muslim fashion retail. The results of the analysis as follows: there is a mismatch in the accounting treatment of PT. Dressmaking when compared with SFAS No. 14, especially in terms of measurement, recognition and disclosure of inventories Keywords: Merchandise Inventory, Inventory Accounting Treatment, SFAS No. 14